RELATIONSHIP BETWEEN HOUSEHOLD ACTIVITIES PERFORMANCE AND BODY MASS INDEX OF HOUSEWIVES - RAJI, ROQEEB BABATUNDE; ADEGBOLA, ABRAHAM; OWOYEMI, ADEBIMPE YETUNDE; SALAWU, OLALEKAN WALIYILAHI; VIJAYASARATHI, GURUPRASAD (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to find out the relationship between household activities performance and body mass index (BMI) of housewives. Methods: This cross-sectional study was undertaken among housewives residing in Shivalli village in Udupi district. The ages of the participants were between 30 and 45 years. The total number of the participants was 61. Household activities performance questionnaire was developed for data collection. The content of the questionnaire was validated by five registered occupational therapists with more than 15 years’ experience. The BMI of the participants was taken to ascertain their body weight status. Semi-structured interview was conducted to inquire about their household tasks using the developed household activities performance questionnaire. A diet chart with a total number of 7 days of meal was collected to calculate the participants’ calorie intake. The corresponding metabolic equivalent of task values for each mentioned task was assigned from compendium of physical activities (PA) to determine the relationship between household activities (manual and mechanical) performance and BMI of the participants. Results: While there was no significant negative correlation between housewives’ household manual activities performance and their BMI, housewives’ household mechanical activities performance and BMI showed a significant positive correlation. Sociodemographic characteristics showed no significant weak negative relationship with BMI score except socio-economic status which showed a significant weak positive relationship. Conclusion: Household activities performed by housewives might not have an impact on their BMI. However, combining household activities with moderate PA might tends to have an impact on the BMI of housewives. Further study with more sample size and a standardized questionnaire is recommended for future study.